Phase stability of a ductile single-phase BCC Hf0.5Nb0.5Ta0.5Ti1.5Zr refractory high-entropy alloy. (July 2018) - Yao, J.Q.; Liu, X.W.; Gao, N.; Jiang, Q.H.; Li, N.; Liu, G.; Zhang, W.B.; Fan, Z.T.
Abstract: High-entropy alloys (HEAs) have attracted much attention since they can possess some unique properties. By adjusting their multi-principal elements, some systems with body centered cubic (BCC) structure could obtain an excellent trade-off of strength and ductility, e.g. recently reported single-phase Hf0.5 Nb0.5 Ta0.5 Ti1.5 Zr refractory high-entropy alloy (RHEA). However, researchers found that some HEAs are thermally metastable and could decompose within a certain temperature range. The thermal stability is especially important for RHEAs which are promising for high-temperature applications. Here we evaluated the phase stability of a BCC Hf0.5 Nb0.5 Ta0.5 Ti1.5 Zr RHEA after anneals for two weeks at 500–900 °C. Microstructural analyses, performed using X-ray diffraction, scanning electron microscopy, high-resolution transparent electron microscopy, show that the RHEA is a single-phase solid solution after recrystallization for 3 h at 1000 °C and remains in this state after a subsequent anneal at 900 °C for two weeks. However, it is unstable and forms second-phase precipitates at and below 800 °C. Tiny precipitates on the grain boundaries (GBs) were observed in the sample annealed at 800 °C. Annealed at 700 °C, precipitates with BCC structure (termed as BCC2) both on the GBs as chains and at intragranular regions as petaloid morphology are present. After the anneal at 500 °C, the RHEA decomposes into multi-phase microstructures with different morphologies: lamellar structure close to the GBs composed of BCC1 and BCC2 phases, and convoluted basket-like structure inside grains comprising a third hexagonal close-packed phase precipitates except for both BCC phases. Thus the phase stability of this RHEA should be carefully evaluated for elevated temperature applications. Highlights: The phase stability of a Hf0.5 Nb0.5 Ta0.5 Ti1.5 Zr BCC high-entropy alloy at 500–900 °C was first studied systematically. The RHEA keeps a single BCC solid solution at as-cast state and during anneals above 900 °C. The phase decomposition into two phases occurs during anneals at 800 and 700 °C. An HCP phase precipitates besides two BCC phases after anneal at 500 °C.